PEMANFAATAN DANA PNPM MANDIRI UNTUK PEMBERDAYAAN EKONOMI MASYARAKAT DESA BULIAN JAYA KECAMATAN MARO SEBO ILIR - Pradina, Alfridea Rahma; Majid, M Nazori; Sucipto, Sucipto (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.07.TAHUN.2025, 2025)
The National Program for Community Empowerment (PNPM Mandiri) is an Indonesian government initiative aimed at reducing poverty through community-based economic empowerment. This study aims to analyze the relationship between the amount of PNPM Mandiri loans and the business development, income improvement, and financial management of beneficiaries in Bulian Jaya Village. A descriptive quantitative approach was employed, with data collected through questionnaires, semi-structured interviews, and documentation. A purposive sample of 34 beneficiaries was selected. The data were analyzed using descriptive statistics, chi-square tests, and logistic regression. The findings reveal that 79.41 percent of respondents experienced business growth, 76.47 percent reported increased income, and 64.71 percent showed improved financial management. Chi-square analysis confirmed a significant relationship between loan amounts and both business development and financial management. These results indicate that loan distribution contributes to improving microeconomic welfare. However, challenges such as low financial literacy, market competition, and fluctuations in raw material prices continue to hinder the program’s long-term effectiveness. The implication is that PNPM Mandiri should be strengthened through financial literacy training, mentoring, and supply chain stabilization to ensure sustainable benefits.